An effect analysis of industry 4.0 to higher education - Baygin, Mehmet; Yetis, Hasan; Karakose, Mehmet; Akin, Erhan (Institute of Electrical and Electronics Engineers Inc., 2016)
From history to the present day, especially in the field of technology is provided a wide range of developments. The most important of these developments has achieved the realization of the industrial revolution, has led to play a leading role in the production is done by human beings. The effects on production of industry 4.0 emerging with this mind is very important. The qualified employees should be trained to make the necessary preparations for the company in this period, it is experiencing the fourth industrial revolution. Therefore, the impacts on higher education of industry 4.0 are examined in this paper. The importance in education of industry 4.0 has revealed with statistical data presented in this study. © 2016 IEEE.
15th International Conference on Information Technology Based Higher Education and Training, ITHET 2016 -- 8 September 2016 through 10 September 2016 -- Istanbul -- 125053
Keywords: curriculum; higher education; Industry 4.0; qualified employees